Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4236/aces.2014.43037
|View full text |Cite
|
Sign up to set email alerts
|

Aromas of <i>Salvia</i> Species Enhance Everyday Prospective Memory Performance in Healthy Young Adults

Abstract: Research has previously demonstrated that aromas of both Salvia officinalis and Salvia lavandulaefolia are capable of modulating aspects of retrospective memory, attention and mood. This study is the first to report the potential for these aromas to enhance everyday prospective memory performance in healthy young adults. In an independent groups design, three conditions, Salvia officinalis aroma, Saliva lavandulaefolia aroma and no aroma were employed with 45 healthy volunteers in each condition. Prospective m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Sage EO has been shown to improve memory performance in a human trial of 45 healthy volunteers accessed by Prospective Remembering Video Procedure (PRVP). The intervention group showed significantly improved performance during the task compared to control groups (Moss, Rouse, & Moss, 2014). Additionally, in a previous study by Moss, Rouse, Wesnes, and Moss (2010), the cognitive performance was assessed via CDR system in 135 healthy patients.…”
Section: Actions Of Eos On the Central Nervous Systemmentioning
confidence: 85%
“…Sage EO has been shown to improve memory performance in a human trial of 45 healthy volunteers accessed by Prospective Remembering Video Procedure (PRVP). The intervention group showed significantly improved performance during the task compared to control groups (Moss, Rouse, & Moss, 2014). Additionally, in a previous study by Moss, Rouse, Wesnes, and Moss (2010), the cognitive performance was assessed via CDR system in 135 healthy patients.…”
Section: Actions Of Eos On the Central Nervous Systemmentioning
confidence: 85%
“…Moss et al demonstrated that Salvia essential oil is likely to affect the level of memory in healthy adults [ 40 , 41 ]. Scholey et al observed that the ethanol leaf extract of S. officinalis improved memory of healthy elderly people [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“… 84 Moss et al reported that the aroma of S. officinalis essential oil could enhance prospective memory performance in healthy adults. 85 , 86 Also, Scholey et al showed that ethanolic extract of this plant improved memory and attention in healthy older subjects. 87 A randomized controlled trial by Akhondzadeh et al showed that a 4-month treatment with hydroalcoholic extract of S. officinalis improved cognitive functions in patients with mild to moderate Alzheimer's disease.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%